Effect of Storage Period on the Microbiological and Sensory Characteristics of Cooked Low Salt White Soft Cheese (Gebna Beyda) - Mohamed Abdalla, Mohamed Osman; Sulieman Mohammed, El Imam Hassan (Pakistan Journal of Nutrition, 2010)
This study was carried out to evaluate the microbial and sensory characteristics of cooked low salt white soft cheese during storage. Low salt cheese was made from pasteurized (72oC/1 min) cow’s milk. After complete coagulation, the curd was cooked at 35oC for 30 min. Cheese was preserved in 2% brine solution for 48 h and then transferred to plastic bags and stored in the refrigerator at 4oC for 60 days. Microbiological examination as well as sensory characteristics was carried out at 1, 20, 40 and 60 day intervals. The results indicated that, during storage period the total viable bacteria count did not show significant change, while psychrotrophic bacteria and yeasts and moulds counts significantly increased throughout storage period. Storage period did not significantly affect the colour, while the flavour, taste, body, saltiness and overall acceptability were significantly affected by the storage period.